Art : a beginner's guide - Adams, Laurie (Oxford : Oneworld, 2012)
From Stone Age statuettes to 21st-century video art, Laurie Schneider Adams unravels the extraordinary story of Western art in this introduction.
Includes bibliographical references p. 199-209 and index.
Keywords: Art -- History; Art criticism